Pengaruh Kepemimpinan Transformasional dan Budaya Organisasi Terhadap Kinerja Keuangan perusahaan dengan dimediasi kepuasan kerja - Antonius Ary Setyawan; Carolina Ety Widjayanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This article conducts a literature review on the relationship between transformational leadership, organizational culture, job satisfaction, and financial performance in companies. Transformational leadership, characterized by vision, inspiration, intellectual stimulation, and individual consideration, has become a key factor in organizational effectiveness. Similarly, organizational culture, encompassing shared values, beliefs, and norms, significantly shapes employee behavior and performance outcomes. The relationship between these leadership styles, organizational culture, and financial performance emphasizes the need for comprehensive understanding and analysis. Additionally, job satisfaction plays a crucial role as a mediator in this relationship. Satisfied employees tend to demonstrate higher levels of productivity, commitment, and innovation, thereby enhancing organizational performance. By mediating between leadership, culture, and financial performance, job satisfaction acts as a bridge connecting organizational practices to tangible outcomes. Through a thorough review of existing literature, this article synthesizes key findings, theoretical frameworks, and empirical evidence to explain the complex dynamics involved. It highlights the importance of fostering transformational leadership and positive organizational culture to strengthen financial performance. Furthermore, it identifies gaps and areas for future research, emphasizing the need for longitudinal studies, cross-cultural analyses, and quantitative assessments to deepen understanding of these complex relationships. Ultimately, this article contributes to the ongoing discourse on leadership, organizational culture, and financial performance, providing insights and implications for both scholars and practitioners. Keywords: Transformational Leadership, Organizational Culture, Job Satisfaction